(untitled) (Sebha University Conference Proceedings, 2024)
In this paper, in real-life situations, the parameters of the linear programming problem model may not be defined precisely, because of the globalization of the market, uncontrollable factors, …etc. For this reason, it was presented an algorithm for solving fuzzy linear fractional programming (FLFP) problems, where coefficients of the objective function and constraints are triangular L-R fuzzy numbers. The FLFP problem can be reduced to a linear fractional programming problem using the ranking function for all triangular L-R fuzzy numbers coefficients, and then using the variable transformation method to obtain an optimal solution with optimum fuzzy objective function. This enables us to obtain many proposed solutions instead of a unique solution, which enables the decision-maker to make the best decisions. A numerical example is given for the sake of illustration.